Limiting effect of diazepam on lewis lung carcinoma metastasis in anxious male mice - Kaledin, V.I.; llnitskaya, S.I.; Nikolin, V.P.; Popova, N.A.; Smagin, D.A.; Kudryavtseva, N.N. (Experimental Oncology, 2009)
Aim: It has been shown previously that chronic social defeat stress produces development ofstrong anxiety and increases intensity of experimental
metastasis in the losers in comparison with the winners and control mice. The question was: isit possible to decrease the number
ofmetastases inthe losers by chronic or acute diazepam treatment. Materials and Methods: Sensory contact model was used for generating
male mice with repeated experience of social victories or defeats in daily agonistic interactions. Tumor cells of Lewis Lung Carcinoma
(LLC) were injected into the tail vein of animals after 10 days of agonistic interactions. Then mice were treated acutely or chronically
(7 days) with diazepam (1 mg/kg, i. p). Number ofmetastases in the lung was calculated in 16 days after tumor cell transplantation. Results:
Diazepam decreased the number of LLC metastases in anxious losers, whereas in the winners and control mice, without anxiety state,
diazepam was ineffective. Conclusion: Well-known anxiolytic diazepam may decrease intensity of metastasis in anxious mice.